Low-sulfur metal cation doped ammonium manganese ferric phosphate precursor, carbon-coated modified sodium manganese ferric pyrophosphate, and preparation method and application of low-sulfur metal cation doped ammonium manganese ferric phosphate precursor and carbon-coated modified sodium manganese ferric pyrophosphate
By preparing low-sulfur metal cation doped with ferrophosphate ammonium manganese phosphate precursor in sodium manganese pyrophosphate material and adding a phosphoric acid source to treat it, the problems of manganese dissolution, high sulfur impurity content and difficulty in embedding of sodium ions in the material are solved, and efficient electrochemical performance improvement is achieved.
Patent Information
- Application Number
- CN202411790661.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The intensified dissolution of manganese sodium manganese pyrophosphate material, high sulfur impurities content, small specific surface area, and difficulty in embedding and disengaging of sodium ions, resulting in poor electrochemical performance.
By using manganese sulfate to provide manganese elements, a low-sulfur metal cation-doped manganese ferroammonium phosphate precursor was prepared, and an appropriate amount of phosphoric acid was added thereto to treat it, and the molar ratio of manganese, iron, doped metal elements and phosphorus elements was regulated to make it slightly less than 1, forming a single solid-solution phase state.
It significantly reduces the sulfur content of the material, improves structural stability and tap density, and enhances the charge and discharge capacity, cycle stability and rate performance of the positive electrode material of sodium ion battery.
Smart Images

Figure CN119591076A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and more specifically, relates to a low-sulfur metal cation-doped ammonium ferric manganese phosphate precursor, a carbon-coated modified sodium ferric manganese phosphate pyrophosphate, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries, as the current mainstream energy storage technology, achieve electrical energy storage through the reversible insertion and deintercalation of lithium ions between the positive and negative electrodes. However, lithium-ion batteries have limited energy storage in the earth's crust, and the growing global demand for clean energy and portable electronic devices has led to a scarcity of lithium resources and rising prices. Although lithium ions excel in energy density, cycle life and comprehensive performance, their high cost and strong resource dependence have prompted researchers to explore alternatives. In this context, sodium-ion batteries have become a strong competitor to lithium-ion batteries with their similar energy storage principles, abundant crustal reserves and lower cost potential. In particular, polyanion-type sodium-ion battery cathode materials are considered to be ideal for high-energy-density sodium-ion batteries due to their abundant raw materials, low cost, stable structure, simple synthesis, high theoretical specific capacity and environmental friendliness. Among them, sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7), as one of the mixed iron-based phosphates, has a higher theoretical specific capacity because of the more alkali metal ions in the material structure than sodium iron phosphate (NaFePO4). However, its poor intrinsic conductivity and low discharge platform limit the full utilization of its energy density.
[0003] In order to increase the voltage platform of sodium iron pyrophosphate, researchers tried to introduce manganese into sodium iron pyrophosphate to replace part of the iron element, thereby forming a solid solution phase of sodium manganese iron pyrophosphate. This strategy combines Mn 2+ The high voltage platform and Fe 2+The advantage of similar ionic radius effectively improves the voltage platform and energy density of mixed iron-based phosphates. However, the conventional manganese doping process is often achieved by adding low-cost sulfate. Although this approach is economical, it will inevitably lead to an increase in the sulfur content in the material, which will have an adverse effect on its electrochemical performance. In addition, sodium manganese iron pyrophosphate also faces problems such as increased manganese dissolution, low ionic and electronic conductivity, and difficulty in sodium ion insertion and extraction, all of which will have an adverse effect on the electrochemical properties of the material. In response to the above problems, the prior art has attempted strategies such as ion doping and carbon coating. On the one hand, Chinese patent application CN118295543A discloses a high compaction density sodium manganese iron pyrophosphate / carbon composite positive electrode material, which synthesizes and prepares nano-spherical particles by a three-step sintering method. Although this material improves the electrochemical properties such as electronic and ionic conductivity and charge and discharge capacity to a certain extent. However, the process is relatively cumbersome and energy-intensive, and the use of carbon coating as an independent step may not be conducive to the in-situ formation of a dense carbon coating layer, which will affect the full utilization of the compaction density and ensure the uniformity of the carbon coating. On the other hand, the high entropy sodium phosphate pyrophosphate sodium ion battery positive electrode material disclosed in Chinese patent application CN116404154A is formed by introducing Mg, Ca, Al, Cr, and Mn in equal molar ratios at the Fe position to form a joint crystal. Although the material has a single phase and good crystallinity, it still faces the problem of difficulty in embedding and extracting sodium ions. This problem not only affects the ionic conductivity and structural stability of the material, but may also aggravate the Jahn-Teller distortion effect, thereby adversely affecting the electrochemical properties of the material. In addition, it can be observed from the SEM image that the positive electrode material has an obvious accumulation phenomenon, which may lead to a significant reduction in the specific surface area of the electrolyte contact and an extension of the sodium ion migration path, which is not conducive to fully utilizing the active material and accelerating the sodium ion migration kinetics, thereby affecting the full play of its electrochemical performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art, such as the aggravated manganese dissolution, high sulfur impurity content, small specific surface area and Jahn-Teller structural distortion caused by the difficulty of sodium ion embedding and release in the sodium ferromanganese phosphate pyrophosphate material, and to provide a preparation method of a low-sulfur metal cation-doped ammonium ferromanganese phosphate precursor.
[0005] Another object of the present invention is to provide a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor prepared by the above preparation method.
[0006] Another object of the present invention is to provide a method for preparing carbon-coated modified sodium manganese iron phosphate pyrophosphate.
[0007] Another object of the present invention is to provide carbon-coated modified sodium manganese iron pyrophosphate prepared by the above preparation method.
[0008] Another object of the present invention is to provide a sodium ion battery positive electrode, the positive electrode comprising the aforementioned carbon-coated modified sodium manganese iron phosphate pyrophosphate.
[0009] Another object of the present invention is to provide a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the positive electrode of the sodium ion battery described above.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] The present invention provides a method for preparing a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, comprising the following steps:
[0012] S1. Using manganese sulfate to provide manganese element to prepare a metal cation-doped ammonium manganese iron phosphate precursor;
[0013] S2. The metal cation-doped ammonium manganese iron phosphate precursor obtained in step S1 is mixed with a phosphoric acid source, the pH of the solution is maintained at 7 to 8, the mixture is fully reacted at 30 to 80° C., filtered, the precipitate is washed, and dried to obtain a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor;
[0014] Wherein, the metal cation is selected from at least one non-repeating member of Ca, Mg, Al, Ti, Ni, Cr, Zn, Mo, Cu, Zr, Nb, Y, Sn, Co, Ce, V, and W;
[0015] The low-sulfur metal cation doped ammonium manganese iron phosphate precursor is expressed as NH4Mn x Fe 1-x-y M y PO4, 0<x<0.9, 0<y<0.1; said M represents one or more metal cation doping;
[0016] The amount of the phosphoric acid source (the amount of which is calculated as phosphate radical) added is at least 0.1 times the amount of the metal cation-doped ammonium manganese iron phosphate precursor;
[0017] The steps S1 to S2 are all performed under a protective gas atmosphere.
[0018] The sodium manganese ferric phosphate pyrophosphate material is often realized by low-cost manganese sulfate during the manganese doping process. Although this approach is economical, it will inevitably cause the problem of excessive sulfur content in the material. This is because sulfur impurities (sulfate) will be wrapped inside the prepared ammonium manganese ferric phosphate precursor particles or adsorbed on the surface, resulting in a high sulfur impurity content in the resulting precursor. The inventors found that adding an appropriate amount of phosphate source to the synthesized metal cation-doped ammonium manganese ferric phosphate precursor can induce recrystallization to expose sulfur impurities and detach from the precursor particles, and then through subsequent filtering and washing post-processing, the transfer of sulfur impurities is achieved, thereby achieving the purpose of removing sulfur impurities. At the same time, the addition of a phosphate source can regulate the metal cation-doped ammonium manganese ferric phosphate precursor NH4Mn x Fe 1-x-y M y The molar ratio of the total molar amount of manganese, iron, and doped metal elements to phosphorus in PO4 is slightly less than 1, which realizes the uniform substitution and coordination of different elements in the precursor. This regulation ensures that the doped metal, manganese, and iron elements are regularly distributed at the atomic level in the precursor lattice, forming a single solid solution phase, thereby further improving the NH4Mn x Fe 1-x-y M y The structural stability of PO4 and greatly reduced its sulfur content.
[0019] Further, as a common expression, the NH4Mn x Fe 1-x-y M y When M in PO4 represents multiple (eg, 4) metal cation doping, A, B, C, and D are used to represent 4 different metal cations respectively.
[0020] Furthermore, as a common expression, when there are four kinds of metal cations doped, the expression of the low-sulfur metal cation doped ammonium manganese iron phosphate precursor is NH4Mn x Fe 1-x-a-b-c-d A a B b C c D d PO4, and 0<x<0.9, 0<a<0.1, 0<b<0.1, 0<c<0.1, 0<d<0.1, a+b+c+d<0.1.
[0021] Further, as a common expression, the NH4Mn x Fe 1-x-y M y When M in PO4 represents multiple (such as 5) metal cation doping, A, B, C, D, and E are used to represent 5 different metal cations respectively.
[0022] Furthermore, as a common expression, when the number of doped metal cations is 5, the expression of the low-sulfur metal cation doped ammonium manganese iron phosphate precursor is NH4Mn x Fe 1-x-a-b-c-d-e A a B b C c D d E e PO4, and 0<x<0.9, 0<a<0.1, 0<b<0.1, 0<c<0.1, 0<d<0.1, 0<e<0.1, a+b+c+d+e<0.1.
[0023] Furthermore, in step S1, the method for preparing the metal cation-doped ammonium manganese iron phosphate precursor comprises the following steps:
[0024] SI. The manganese sulfate, doped metal cation salt solution M is prepared under a protective gas atmosphere to form a mixed solution I;
[0025] SII. The iron element and the phosphoric acid source solution are fully reacted under a protective gas atmosphere to obtain a ferrous dihydrogen phosphate solution system II;
[0026] SIII. Under a protective gas atmosphere, the mixed solution I obtained in step SI and the oxidant are added to the dihydrogen phosphate solution system II obtained in step SII, mixed, and fully reacted at 50-80° C. to oxidize the divalent manganese ions and the divalent iron ions to trivalent manganese ions and trivalent iron ions, respectively, to obtain an intermediate system III. After adjusting the pH of the intermediate system III to 7-8, react at 50-80° C., and post-treat to obtain a metal cation-doped ammonium manganese iron phosphate precursor.
[0027] Furthermore, in step SI, the metal cation salt M solution includes one or more of sulfate, citrate, nitrate, carbonate, bicarbonate, ammonium salt, acetate, phosphate, and oxalate.
[0028] Furthermore, in step S1, the Ca is selected from calcium chloride, calcium nitrate, calcium acetate, calcium bicarbonate, calcium dihydrogen phosphate or a hydrate of any of the above calcium salts.
[0029] Further, in step S1, the Mg is selected from magnesium sulfate, magnesium chloride, magnesium nitrate, magnesium carbonate, magnesium oxalate, magnesium acetate, magnesium citrate or a hydrate of any of the above magnesium salts.
[0030] Furthermore, in step S1, the Al is selected from aluminum sulfate, aluminum chloride, aluminum nitrate or a hydrate of any of the above aluminum salts.
[0031] Furthermore, in step SI, the Ti is selected from ammonium titanium oxalate, titanium sulfate, titanium oxysulfate, titanium chloride or a hydrate of any of the above titanium salts.
[0032] Further, in step S1, the Ni is selected from nickel sulfate, nickel nitrate, nickel acetate, nickel chloride or a hydrate of any of the above nickel salts.
[0033] Furthermore, in step S1, the Cr is selected from chromium sulfate, chromium chloride, chromium oxalate, chromium acetate or a hydrate of any of the above chromium salts.
[0034] Further, in step S1, the Zn is selected from zinc sulfate, zinc acetate, zinc chloride, zinc nitrate or a hydrate of any of the above zinc salts.
[0035] Further, in step S1, the Mo is selected from ammonium molybdate, molybdenum sulfate, molybdenum chloride, molybdenum nitrate, molybdenum acetate or a hydrate of any of the above molybdenum salts.
[0036] Further, in step S1, the Cu is selected from copper sulfate, copper acetate, copper chloride, copper nitrate or a hydrate of any of the above copper salts.
[0037] Furthermore, in step S1, the Zr is selected from zirconium sulfate, zirconium tetrachloride, zirconium oxychloride, zirconium nitrate, zirconium acetate or a hydrate of any of the above zirconium salts.
[0038] Furthermore, in step S1, the Nb is selected from ammonium niobium oxalate, niobium oxalate or a hydrate of any of the above niobium salts.
[0039] Further, in step SI, the Y is selected from yttrium sulfate, yttrium nitrate, yttrium chloride, yttrium acetate or a hydrate of any of the above yttrium salts.
[0040] Furthermore, in step S1, the Sn is selected from stannous sulfate, stannous chloride, stannous acetate, tin nitrate or a hydrate of any of the above tin salts.
[0041] Furthermore, in step S1, the Co is selected from cobalt sulfate, cobalt acetate, cobalt chloride, cobalt nitrate or a hydrate of any of the above cobalt salts.
[0042] Furthermore, in step SI, the Ce is selected from cerium sulfate, cerium nitrate, cerium acetate, cerium oxalate, cerium chloride or a hydrate of any of the above cerium salts.
[0043] Further, in step SI, the V is selected from vanadium oxalate, vanadium sulfate, vanadium dichloride or a hydrate of any of the above vanadium salts.
[0044] Furthermore, in step S1, the W is selected from tungsten nitrate, tungsten chloride, tungsten phosphate or a hydrate of any of the above tungsten salts.
[0045] Further, in step SI, the molar ratio of manganese in the manganese sulfate to the doped cations in the doped metal cation salt M solution is f:g, where 0 < f < 0.9 and 0 < g < 0.1.
[0046] Further, in step SI, the molar concentration of the mixed solution I is the molar concentration of the total metal cations.
[0047] Furthermore, in step SI, the concentration of the mixed solution I is 0.1 - 5 mol / L, preferably 3 mol / L.
[0048] Further, in step SI, the protective gas includes one or more of nitrogen, helium, and argon.
[0049] Further, in step SII, the elemental iron is sourced from one or more of iron blocks, iron powders, iron slags, iron sheets, and iron foils.
[0050] Further, in step SII, the phosphoric acid source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, lithium phosphate, sodium phosphate, ammonium hypophosphite, ammonium polyphosphate, sodium phosphite, sodium metaphosphate, and sodium tripolyphosphate.
[0051] Further, in step SII, the molar ratio of the elemental iron to the phosphoric acid source is 1:(1 - 3).
[0052] Further, in step SII, the time for sufficient reaction is 0.5 - 10 h.
[0053] Further, in step SII, since the oxidizing property of the phosphoric acid source is weak and in an atmosphere of protective gas, the elemental iron is only oxidized to the divalent state, and thus ferrous dihydrogen phosphate is formed.
[0054] Further, in step SIII, the oxidant includes one or more of hydrogen peroxide, oxygen, and ozone. Adding an oxidant, one of the purposes is to oxidize Mn in the divalent manganese salt in the mixed solution I obtained in step SI by the oxidant to Mn 2+ ; another purpose is to oxidize Fe in the ferrous dihydrogen phosphate solution system II obtained in step SII to Fe 3+ ; 2+ ; 3+ .
[0055] Further, in step SIII, the molar ratio of the oxidant is at least 0.5 times the molar amount of manganese sulfate in the mixed solution I obtained in step SI.
[0056] Further, in step SIII, the time for sufficient reaction is 0.5 - 10 h.
[0057] Furthermore, in step SIII, the pH 7-8 is adjusted by adding an alkaline reagent.
[0058] Furthermore, the alkaline reagent includes one or more of urea, ammonia, and urea phosphate. By using these alkaline reagents to adjust the solution pH, Mn 3+ and Fe 3+ It is co-precipitated with the doped metal cations in the phosphate system to form a uniform metal cation-doped ammonium manganese iron phosphate precursor, while also avoiding the use of sodium hydroxide, potassium hydroxide, etc. to introduce alkali metal impurities such as Na and K.
[0059] Furthermore, in step SIII, the reaction time is 0.5 to 10 h.
[0060] Furthermore, in step SIII, the post-treatment includes filtering, washing and drying.
[0061] Furthermore, the filtration is filter pressing, that is, the solution containing the metal cation-doped ammonium manganese ferric phosphate precursor is filtered pressing and then the solid-liquid separation is performed.
[0062] Furthermore, the washing is washing the filtered filter cake with water for 3 to 5 times.
[0063] Furthermore, the drying is flash evaporation, that is, the washed filter cake is transferred into a flash evaporator for heat and moisture exchange to quickly evaporate the surface moisture.
[0064] Specifically, in step SIII, the post-treatment includes filtering the solution containing the metal cation-doped ammonium manganese iron phosphate precursor and then separating the solid and liquid, washing the filter cake after filtering with water for 3 to 5 times, and transferring the washed filter cake into a flash evaporator for wet heat exchange to quickly evaporate the surface moisture.
[0065] Further, in step S2, the phosphate source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, ammonium phosphate, lithium phosphate, sodium phosphate, ammonium hypophosphite, ammonium polyphosphate, sodium phosphite, sodium metaphosphate, and sodium tripolyphosphate.
[0066] Furthermore, in step S2, the molar ratio of the metal cation-doped ammonium manganese iron phosphate precursor to the phosphoric acid source is 1: (0.1-20), and this ratio is intended to ensure that the phosphoric acid source is excessive relative to the precursor. If the phosphoric acid source is added in excessive amounts, it will cause unnecessary waste of resources.
[0067] Furthermore, in step S2, the mixing time is 10 to 180 minutes.
[0068] Furthermore, in step S2, the pH value of 7 to 8 is adjusted by adding an alkaline reagent.
[0069] Furthermore, the alkaline reagent is one or more of urea, ammonia water, and urea phosphate.
[0070] Furthermore, in step S2, the sufficient reaction time is 0.5 to 10 hours.
[0071] Furthermore, in step S2, the filtration is filter pressing, that is, the solution containing the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor is filtered pressing and then solid-liquid separation is performed.
[0072] Furthermore, in step S2, the precipitate washing is washing the filtered precipitate with water for 3 to 5 times.
[0073] Furthermore, in step S2, the drying is flash evaporation, that is, the washed precipitate is transferred into a flash evaporator for heat and moisture exchange to quickly evaporate surface moisture.
[0074] The present invention protects a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor prepared by the above preparation method.
[0075] The present invention synthesizes a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor NH4Mn x Fe 1-x-y M y PO4. The precursor significantly reduces the sulfur impurity content by treating the prepared metal cation-doped ammonium manganese iron phosphate precursor with an appropriate amount of phosphoric acid source, reaching the battery grade standard. At the same time, the addition of the phosphoric acid source allows the actual molar ratio of manganese, iron and doped metal elements to phosphorus in the precursor to be regulated to slightly less than 1. This ratio effectively improves the stability of the precursor structure, allowing each doping element and the main element (manganese and iron) to be distributed at the atomic level in the precursor, and greatly improves the tap density, which is conducive to further preparing positive electrode materials with excellent battery capacity, long cycle life and high safety.
[0076] The present invention provides a method for preparing carbon-coated modified sodium manganese iron pyrophosphate, comprising the following steps:
[0077] Si. The sodium salt, the phosphate source, the aforementioned low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, the carbon source and the alcohol solution are fully mixed to obtain a slurry, and the obtained slurry is ground and dried to obtain a powder;
[0078] Sii. Under a protective gas atmosphere, the powder obtained in step Si is pre-calcined at 300-400° C. for 0.5-8 h, then heated to 450-750° C. for full calcination, and post-treated to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate.
[0079] This application can prepare carbon-coated modified sodium manganese iron phosphate pyrophosphate positive electrode material by coprecipitation-one-step sintering method, which is innovative and efficient. During the preparation process, a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor is used as a metal source and a phosphoric acid source, and the periodic distribution between each doping element and the main element in the precursor can be accurately controlled. By combining a carbon layer, a sodium salt, and grinding and spraying treatments, and then calcining, manganese, iron and doped metal cations can be evenly distributed at the crystal level. This preparation method not only significantly enhances the stability of the crystal structure, but also improves the conductivity of the material, ensuring the single solid solution phase characteristics of the positive electrode material.
[0080] Furthermore, in step Si, the sodium salt includes one or more of sodium carbonate, sodium dihydrogen phosphate, sodium bicarbonate, sodium citrate, sodium hydroxide, sodium citrate, sodium pyrophosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium nitrate, sodium chloride, sodium oxalate, and sodium ethoxide.
[0081] Further, in step Si, the phosphate source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, lithium phosphate, sodium pyrophosphate, ammonium hypophosphite, ammonium polyphosphate, ammonium hexafluorophosphate, sodium phosphite, sodium metaphosphate, sodium tripolyphosphate, and sodium hexaphosphate.
[0082] Furthermore, in step Si, the carbon source includes one or more of polyethylene glycol, glucose, fructose, sucrose, starch, cyclodextrin, citric acid, tartaric acid, ascorbic acid, malic acid, lactic acid, polyvinyl pyrrolidone, polyvinylidene fluoride, epoxy resin, and phenolic resin.
[0083] Furthermore, in step Si, the molar ratio of the phosphate source, the sodium salt, and the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor obtained above is 1:(1.3-1.4):(1.3-1.4). The sodium salt and the phosphate source are appropriately added in excess to ensure that the reaction is fully and completely carried out.
[0084] Furthermore, in step Si, the mass ratio of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor to the carbon source is 1: (0.01-1).
[0085] Furthermore, in step S1, the alcohol solution is a mixed solution of an alcohol reagent and water, wherein the alcohol reagent not only serves as a dispersion medium, but also contributes to the rapid drying of the solution due to its faster volatilization rate.
[0086] Furthermore, the alcohol reagent includes one or more of methanol, ethanol, and ethylene glycol.
[0087] Preferably, the alcohol reagent is ethanol.
[0088] More preferably, the volume ratio of the alcohol reagent to water is 1:(1-5).
[0089] Furthermore, in step Si, the solid content of the slurry is 10% to 50%.
[0090] Furthermore, in step Si, the particle size of the ground slurry is 0.2 μm ≤ D 50 ≤0.3μm.
[0091] Furthermore, in step Si, the drying is spray drying.
[0092] Furthermore, the spray drying conditions are as follows: the inlet air temperature is 190-250°C, the outlet air temperature is 90-140°C, and the outlet particle size is 18 μm ≤ D 50 ≤25μm.
[0093] Furthermore, in step Sii, the protective gas includes one or more of nitrogen, helium, and argon.
[0094] Furthermore, in step Sii, the calcining equipment is a box furnace, a roller kiln or a tube furnace, preferably a box furnace.
[0095] Furthermore, the heating rate of the calcination is 1 to 20°C / min.
[0096] Furthermore, in step Sii, the sufficient calcination time is 2 to 20 hours. The staged calcination method is conducive to the formation of a single phase of the carbon-coated modified sodium manganese iron phosphate pyrophosphate.
[0097] Furthermore, in step Sii, the post-processing includes crushing and screening.
[0098] Furthermore, the pulverization is to pulverize the calcined powder to a particle size of 0.6 μm ≤ D 50 ≤0.85μm.
[0099] Furthermore, the sieving is to sifte the crushed powder through a sieve with a mesh size of 200 to 400.
[0100] Specifically, in step Sii, the post-treatment includes crushing the calcined powder to a particle size of 0.6 μm ≤ D 50 ≤0.85μm, and then sieve with a 200-400 mesh sieve.
[0101] The present invention protects the carbon-coated modified sodium manganese iron pyrophosphate prepared by the above preparation method.
[0102] The present invention protects a sodium ion battery positive electrode, comprising a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material comprises the aforementioned carbon-coated modified sodium manganese iron phosphate pyrophosphate.
[0103] Preferably, the current collector is aluminum foil or carbon-coated aluminum foil.
[0104] Furthermore, as a preferred manner, the preparation method of the positive electrode of the sodium ion battery comprises the following steps: dispersing the carbon-coated modified sodium ferromanganese phosphate pyrophosphate, the conductive agent carbon black, and the binder polyvinylidene fluoride in an N-methylpyrrolidone dispersant to obtain a positive electrode slurry, and then coating it on an aluminum foil, and vacuum drying it at 80 to 140° C. for 12 to 24 hours to obtain a positive electrode.
[0105] Furthermore, the mass ratio of the carbon-coated sodium manganese iron pyrophosphate, the conductive agent carbon black, and the binder polyvinylidene fluoride is 1: (0.01-0.29): (0.01-0.14).
[0106] The present invention protects a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode of the sodium ion battery mentioned above.
[0107] The sodium ion battery prepared by the present invention exhibits excellent charge and discharge capacity, capacity retention rate and cycle stability.
[0108] Furthermore, as a preferred embodiment, the positive electrode of the sodium ion battery is the aforementioned sodium ion battery positive electrode, the negative electrode is a metallic sodium sheet, the separator is glass fiber, and the electrolyte is 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0109] Compared with the prior art, the present invention has the following beneficial effects:
[0110] The present application provides a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor. By adding an appropriate amount of phosphoric acid source to the prepared metal cation-doped ammonium manganese iron phosphate precursor, not only the sulfur content of the precursor is significantly reduced, but also the molar ratio of manganese, iron, doping elements and phosphorus elements is regulated to be slightly less than 1, which not only realizes the atomic-level distribution of elements in the precursor, but also improves the tap density, which is conducive to the subsequent preparation of high-performance carbon-coated modified sodium manganese iron phosphate pyrophosphate materials. The sodium ion battery constructed based on this material has excellent charge and discharge capacity, capacity retention rate and cycle stability. In addition, the preparation method of the precursor is simple to operate, easy to control, and exhibits a wide range of application advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0111] Figure 1 The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor NH4Mn prepared in Example 1 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co0.01 Ni 0.01 Cu 0.01 SEM image of PO4. DETAILED DESCRIPTION
[0112] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0113] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0114] Example 1 Preparation of low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0115] 1. Low-sulfur metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co 0.01 Ni 0.01 Cu 0.01 Preparation of PO4.
[0116] Add 7 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 3.39 kg of manganese sulfate monohydrate, 34.51 g of anhydrous magnesium sulfate, 79.12 g of ammonium titanium oxalate, 80.59 g of cobalt sulfate heptahydrate, 75.36 g of nickel sulfate hexahydrate, and 45.76 g of anhydrous copper sulfate in the dissolving tank to prepare a mixed metal source solution I;
[0117] 401.38g of iron block and iron powder mixture were added to a closed synthetic reactor containing 8.49L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 3.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate solution system II was slowly heated to 70°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 70°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to pH 7 with a urea solution and aged for 2h at 70°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co0.01 Ni 0.01 Cu 0.01 PO4).
[0118] Under nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor was dispersed in 20L ultrapure water in a high-efficiency closed synthesis reactor, and 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 3:1. The precursor slurry was stirred for 30 minutes to obtain intermediate system V, and urea was used to adjust the intermediate system V to pH 7, and aged for 4 hours at 70°C under nitrogen atmosphere. Low-sulfur metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co 0.01 Ni 0.01 Cu 0.01 PO4).
[0119] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 2.1 Fe 0.75 Mg 0.03 Ti 0.03 Co 0.03 Ni 0.03 Cu 0.03 Preparation of (PO4)2P2O7
[0120] The corresponding sodium carbonate, low-sulfur metal cation-doped ammonium manganese iron phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+Mg+Ti+Co+Ni+Cu): P of 4.08:3:4.05, and an organic carbon source polyethylene glycol (5.1wt% of the mass of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor) was added. After stirring for 15 minutes until the dispersion was uniform, the slurry with a solid content of 40% was transferred into a sand mill and ground to a particle size D 50 When the particle size is 0.25 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to staged temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 380°C at a heating rate of 5°C / min and kept for 3 hours, and then the temperature is raised to 500°C at a heating rate of 5°C / min and kept for 8 hours.
[0121] After the atmosphere box furnace is cooled to room temperature naturally, the sintered powder is jet-milled and sieved to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 2.1 Fe 0.75 Mg0.03 Ti 0.03 Co 0.03 Ni 0.03 Cu 0.03 (PO4)2P2O7).
[0122] 3. Preparation of sodium ion batteries
[0123] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on an aluminum foil and vacuum dried at 120°C for 12 hours to obtain a sodium ion battery positive electrode.
[0124] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0125] Example 2 Preparation of low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron phosphate pyrophosphate and sodium ion battery
[0126] 1. Low-sulfur metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.75 Fe 0.2 W 0.01 Nb 0.01 Co 0.01 Zn 0.01 Cu 0.01 Preparation of PO4
[0127] Add 9 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 4.54 kg of manganese sulfate monohydrate, 105.3 g of sodium tungstate, 192.8 g of niobium oxalate, 100.7 g of cobalt sulfate hexahydrate, 64.38 g of zinc sulfate monohydrate, and 57.2 g of anhydrous copper sulfate in the dissolving tank to prepare a mixed metal source solution I;
[0128] 401.38g of iron block and iron powder mixture were added to a closed synthetic reactor containing 7.67L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 4.13kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate solution system II was slowly heated to 76°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 76°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to a pH of 7.5 with a urea solution and aged for 2h at 76°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.75 Fe 0.2 W 0.01 Nb 0.01 Co 0.01 Zn 0.01 Cu 0.01 PO4).
[0129] Under nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor was dispersed in 20L ultrapure water in a high-efficiency closed synthesis reactor, and 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 4:1. The precursor slurry was stirred for 30 minutes to obtain the intermediate system V, and urea was used to adjust the pH of system V to 7.5 and aged for 4 hours at 76°C under nitrogen atmosphere. The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.75 Fe 0.2 W 0.01 Nb 0.01 Co 0.01 Zn 0.01 Cu 0.01 PO4).
[0130] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 2.25 Fe 0.6 W 0.03 Nb 0.03 Co 0.03 Zn 0.03 Cu 0.03 Preparation of (PO4)2P2O7
[0131] The corresponding sodium carbonate, low-sulfur metal cation-doped ammonium manganese iron phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+W+Nb+Co+Zn+Cu): P of 4.06:3:4.06, and an organic carbon source polyethylene glycol (4.8wt% of the mass of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor) was added. After stirring for 15 minutes until the dispersion was uniform, the slurry with a solid content of 38% was transferred into a sand mill and ground to a particle size D 50 When the particle size is 0.28 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 360°C at a heating rate of 5°C / min and kept for 2 hours, and then the temperature is raised to 520°C at a heating rate of 5°C / min and kept for 9 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 2.25 Fe 0.6 W 0.03 Nb 0.03 Co 0.03 Zn 0.03 Cu 0.03 (PO4)2P2O7).
[0132] 3. Preparation of sodium ion batteries
[0133] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0134] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0135] Example 3 Preparation of low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron phosphate pyrophosphate and sodium ion battery
[0136] 1. Low-sulfur metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.25 Fe 0.7 Mg 0.01 Ti 0.02 Co 0.01 Zn 0.01 Preparation of PO4
[0137] 1 L of ultrapure water was added to a nitrogen-filled dissolving tank, and 432.64 g of manganese sulfate monohydrate, 12.32 g of anhydrous magnesium sulfate, 56.51 g of ammonium titanium oxalate, 28.79 g of cobalt sulfate hexahydrate, and 18.4 g of zinc sulfate monohydrate were dissolved in the above dissolving tank to prepare a mixed metal source solution I;
[0138] 401.38g of iron block and iron powder mixture was added to a sealed synthetic reactor containing 10.62L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 1.18kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 74°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 74°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to a pH of 7.2 with a urea solution and aged for 2h at 74°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.25 Fe 0.7 Mg 0.01 Ti 0.02 Co 0.01 Zn 0.01 PO4).
[0139] Under nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor was dispersed in 20L ultrapure water in a high-efficiency closed synthesis reactor, and 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 3.5:1. The precursor slurry was stirred for 30min to obtain the intermediate system V, and urea was used to adjust the pH of system V to 7.2 and aged for 4h at 74℃ under nitrogen atmosphere. The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.25 Fe 0.7 Mg 0.01 Ti 0.02 Co 0.01 Zn 0.01 PO4).
[0140] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 0.75 Fe 2.1 Mg 0.03 Ti 0.06 Co 0.03 Zn 0.03Preparation of (PO4)2P2O7
[0141] The corresponding sodium carbonate, low-sulfur metal cation-doped ammonium manganese iron phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn + Fe + Mg + Ti + Co + Zn): P of 4.09:3:4.09, and an organic carbon source polyethylene glycol (4.8 wt% of the mass of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor) was added. After stirring for 15 min until the dispersion was uniform, the slurry with a solid content of 38% was transferred into a sand mill and ground to a particle size D 50 When the particle size is 0.26 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 360°C at a heating rate of 5°C / min and kept for 2 hours, and then the temperature is raised to 550°C at a heating rate of 5°C / min and kept for 9 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 0.75 Fe 2.1 Mg 0.03 Ti 0.06 Co 0.03 Zn 0.03 (PO4)2P2O7).
[0142] 3. Preparation of sodium ion batteries
[0143] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0144] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0145] Example 4 Preparation of low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0146] 1. Low-sulfur metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.7 Fe 0.25 V 0.05 Preparation of PO4
[0147] Add 7 L of ultrapure water into a dissolving tank filled with nitrogen, and dissolve 3.39 kg of manganese sulfate monohydrate and 443.18 g of vanadyl oxalate in the dissolving tank to prepare a mixed metal source solution I;
[0148] 401.38g of iron block and iron powder mixture was added to a closed synthetic reactor containing 8.49L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 3.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 74°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 74°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to a pH of 7.2 with a urea solution and aged for 2h at 74°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.7 Fe 0.25 V 0.05 PO4).
[0149] Under nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor was dispersed in 20L ultrapure water in a high-efficiency closed synthesis reactor, and 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 3:1. The precursor slurry was stirred for 30 minutes to obtain the intermediate system V, and urea was used to adjust the pH of system V to 7.2 and aged for 4 hours at 74°C under nitrogen atmosphere. The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.7 Fe 0.25 V 0.05 PO4).
[0150] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 2.1 Fe 0.75 V 0.15 Preparation of (PO4)2P2O7
[0151] The corresponding sodium carbonate, low-sulfur metal cation-doped ammonium manganese iron phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn + Fe + V): P of 4.09:3:4.09, and an organic carbon source polyethylene glycol (4.8 wt% of the mass of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor) was added. After stirring for 15 min until the dispersion was uniform, the slurry with a solid content of 38% was transferred to a sand mill and ground to a particle size D 50 When the particle size is 0.26 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 360°C at a heating rate of 5°C / min and kept for 2 hours, and then the temperature is raised to 550°C at a heating rate of 5°C / min and kept for 9 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 2.1 Fe 0.75 V 0.15 (PO4)2P2O7).
[0152] 3. Preparation of sodium ion batteries
[0153] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0154] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0155] Comparative Example 1 Preparation of metal cation-doped manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0156] The difference from Example 1 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with a phosphoric acid source solution, that is, the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor NH4Mn is not prepared. 0.7 Fe 0.25 Mg 0.0 1Ti 0.01 Co 0.01 Ni 0.01 Cu 0.01 PO4. The specific steps are as follows:
[0157] 1. Metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co 0.01 Ni 0.01 Cu 0.01 Preparation of PO4
[0158] Add 7 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 3.39 kg of manganese sulfate monohydrate, 34.51 g of anhydrous magnesium sulfate, 79.12 g of titanium oxalate, 80.59 g of cobalt sulfate heptahydrate, 75.36 g of nickel sulfate hexahydrate, and 45.76 g of anhydrous copper sulfate in the dissolving tank to prepare a mixed metal source solution I;
[0159] 401.38g of iron block and iron powder mixture was added to a closed synthetic reactor containing 8.49L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 3.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 70°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 70°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to pH 7 with a urea solution and aged for 2h at 70°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.7 Fe 0.25 Mg 0.01 Ti 0.01 Co 0.01 Ni 0.01 Cu 0.01 PO4).
[0160] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 2.1 Fe 0.75 Mg 0.03 Ti 0.03 Co 0.03 Ni 0.03 Cu 0.03 Preparation of (PO4)2P2O7
[0161] The corresponding sodium carbonate, metal cation-doped ammonium manganese ferric phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+Mg+Ti+Co+Ni+Cu): P of 4.08:3:4.05, and an organic carbon source polyethylene glycol (5.1wt% of the mass of the metal cation-doped ammonium manganese ferric phosphate precursor) was added. After stirring for 15 minutes until the dispersion was uniform, the slurry with a solid content of 40% was transferred into a sand mill and ground to a particle size of D 50 When the particle size is 0.25 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 380°C at a heating rate of 5°C / min and kept for 3 hours, and then the temperature is raised to 500°C at a heating rate of 5°C / min and kept for 8 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 2.1 Fe 0.75 Mg 0.03 Ti 0.03 Co 0.03 Ni 0.03 Cu 0.03 (PO4)2P2O7).
[0162] 3. Preparation of sodium ion batteries
[0163] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0164] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0165] Comparative Example 2 Preparation of metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0166] The difference from Example 2 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with a phosphoric acid source solution, that is, the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor NH4Mn is not prepared. 0.75 Fe 0.2 W 0.01 Nb 0.01Co 0.01 Zn 0.01 Cu 0.01 PO4. The specific steps are as follows:
[0167] 1. Metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.75 Fe 0.2 W 0.01 Nb 0.01 Co 0.01 Zn 0.01 Cu 0.01 Preparation of PO4
[0168] Add 9 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 4.54 kg of manganese sulfate monohydrate, 105.3 g of sodium tungstate, 192.8 g of niobium oxalate, 100.7 g of cobalt sulfate hexahydrate, 64.38 g of zinc sulfate monohydrate, and 57.2 g of anhydrous copper sulfate in the dissolving tank to prepare a mixed metal source solution I;
[0169] 401.38g of iron block and iron powder mixture was added to a closed synthetic reactor containing 7.67L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 4.13kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 76°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 76°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to a pH of 7.5 with a urea solution and aged for 2h at 76°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.75 Fe 0.2 W 0.01 Nb 0.01 Co 0.01 Zn 0.01 Cu 0.01 PO4).
[0170] 2. Carbon-coated modified phosphoric acid is called sodium iron manganese phosphate Na4Mn 2.25 Fe 0.6 W 0.03 Nb 0.03 Co 0.03 Zn 0.03 Cu 0.03 Preparation of (PO4)2P2O7
[0171] The corresponding sodium carbonate, metal cation-doped ammonium manganese ferric phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+W+Nb+Co+Zn+Cu): P of 4.06:3:4.06, and an organic carbon source polyethylene glycol (4.8 wt% of the mass of the metal cation-doped ammonium manganese ferric phosphate precursor) was added. After stirring for 15 min until the dispersion was uniform, the slurry with a solid content of 38% was transferred to a sand mill and ground to a particle size of D 50 When the particle size is 0.28 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 360°C at a heating rate of 5°C / min and kept for 2 hours, and then the temperature is raised to 520°C at a heating rate of 5°C / min and kept for 9 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 2.25 Fe 0.6 W 0.03 Nb 0.03 Co 0.03 Zn 0.03 Cu 0.03 (PO4)2P2O7).
[0172] 3. Preparation of sodium ion batteries
[0173] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0174] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0175] Comparative Example 3 Preparation of metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0176] The difference from Example 3 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with a phosphoric acid source solution, that is, the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor NH4Mn is not prepared. 0.25 Fe 0.7 Mg 0.0 1Ti 0.02Co 0.01 Zn 0.01 PO4. The specific steps are as follows:
[0177] 1. Metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.25 Fe 0.7 Mg 0.01 Ti 0.02 Co 0.01 Zn 0.01 Preparation of PO4
[0178] 1 L of ultrapure water was added to a nitrogen-filled dissolving tank, and 432.64 g of manganese sulfate monohydrate, 12.32 g of anhydrous manganese sulfate, 56.51 g of ammonium titanium oxalate, 28.79 g of cobalt sulfate hexahydrate, and 18.4 g of zinc sulfate monohydrate were dissolved in the above dissolving tank to prepare a mixed metal source solution I;
[0179] 401.38g of iron block and iron powder mixture was added to a sealed synthetic reactor containing 10.62L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 1.18kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 74°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 74°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to a pH of 7.2 with a urea solution and aged for 2h at 74°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.25 Fe 0.7 Mg 0.01 Ti 0.02 Co 0.01 Zn 0.01 PO4).
[0180] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 0.75 Fe 2.1 Mg 0.03 Ti 0.06 Co 0.03 Zn 0.03 Preparation of (PO4)2P2O7
[0181] The corresponding sodium carbonate, metal cation-doped ammonium manganese ferric phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+Mg+Ti+Co+Zn): P of 4.09:3:4.09, and an organic carbon source polyethylene glycol (4.8wt% of the mass of the metal cation-doped ammonium manganese ferric phosphate precursor) was added. After stirring for 15 minutes until the dispersion was uniform, the slurry with a solid content of 38% was transferred to a sand mill and ground to a particle size of D 50 When the particle size is 0.26 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 360°C at a heating rate of 5°C / min and kept for 2 hours, and then the temperature is raised to 550°C at a heating rate of 5°C / min and kept for 9 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 0.75 Fe 2.1 Mg 0.03 Ti 0.06 Co 0.03 Zn 0.03 (PO4)2P2O7).
[0182] 3. Preparation of sodium ion batteries
[0183] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0184] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0185] Comparative Example 4 Preparation of metal cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified sodium manganese iron pyrophosphate and sodium ion battery
[0186] The difference from Example 1 is that in step 1, an excess amount of metal cations is used to dope with ammonium manganese ferric phosphate to prepare a metal cation-doped ammonium manganese ferric phosphate precursor. The specific steps are as follows:
[0187] 1. Metal cation doped ammonium manganese iron phosphate precursor NH4Mn 0.5 Fe 0.25 Mg0.05 Ti 0.05 Co 0.05 Ni 0.05 Cu 0.05 Preparation of PO4
[0188] Add 7 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 2.42 kg of manganese sulfate monohydrate, 172.55 g of anhydrous magnesium sulfate, 420.42 g of ammonium titanium oxalate, 402.95 g of cobalt sulfate heptahydrate, 376.8 g of nickel sulfate hexahydrate, and 228.8 g of anhydrous copper sulfate in the dissolving tank to prepare a mixed metal source solution I;
[0189] 401.38g of iron block and iron powder mixture was added to a closed synthetic reactor containing 8.49L of ultrapure water, nitrogen was introduced into the reactor and stirred continuously, and then 3.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped in, and stirred evenly for 1h to obtain ferrous dihydrogen phosphate solution system II. The ferrous dihydrogen phosphate system II was slowly heated to 70°C, and the metal: hydrogen peroxide (2.1kg 27.5wt%) in the mixed metal source solution I was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1. After being fully stirred and reacted for 2h at 70°C under a nitrogen protective atmosphere, an intermediate system III was obtained. The intermediate system III was then adjusted to pH 7 with a urea solution and aged for 2h at 70°C under a nitrogen protective atmosphere to obtain a doped modified manganese iron phosphate slurry. The metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.5 Fe 0.25 Mg 0.05 Ti 0.05 Co 0.05 Ni 0.05 Cu 0.05 PO4).
[0190] Under nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor was dispersed in 20L ultrapure water in a high-efficiency closed synthesis reactor, and 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 3:1. The precursor slurry was stirred for 30 minutes to obtain the intermediate system V, and urea was used to adjust the pH of system V to 7 and aged for 4 hours at 70°C under nitrogen atmosphere. The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor (NH4Mn 0.5 Fe 0.25 Mg 0.05 Ti 0.05 Co 0.05 Ni 0.05 Cu 0.05 PO4).
[0191] 2. Carbon-coated modified sodium manganese iron pyrophosphate Na4Mn 1.5 Fe 0.75 Mg 0.15 Ti 0.15 Co 0.15 Ni 0.15 Cu 0.15 Preparation of (PO4)2P2O7
[0192] The corresponding sodium carbonate, metal cation-doped ammonium manganese ferric phosphate precursor and sodium dihydrogen phosphate were weighed in a mixed solution of ultrapure water and ethanol (the volume ratio of ultrapure water and ethanol was 1:1) with a mass ratio of Na: (Mn+Fe+Mg+Ti+Co+Ni+Cu): P of 4.08:3:4.05, and an organic carbon source polyethylene glycol (5.1wt% of the mass of the metal cation-doped ammonium manganese ferric phosphate precursor) was added. After stirring for 15 minutes until the dispersion was uniform, the slurry with a solid content of 40% was transferred into a sand mill and ground to a particle size of D 50 When the particle size is 0.25 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder is subjected to segmented temperature sintering in an atmosphere box furnace under a nitrogen protective atmosphere. The temperature is raised to 380°C at a heating rate of 5°C / min and kept for 3 hours, and then the temperature is raised to 500°C at a heating rate of 5°C / min and kept for 8 hours. After naturally cooling to room temperature, the sintered powder obtained from the furnace is subjected to air flow crushing and sieving to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate (Na4Mn 1.5 Fe 0.75 Mg 0.15 Ti 0.15 Co 0.15 Ni 0.15 Cu 0.15 (PO4)2P2O7).
[0193] 3. Preparation of sodium ion batteries
[0194] The carbon-coated modified sodium manganese iron phosphate pyrophosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 90:5:5 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 100°C for 24 hours to obtain a sodium ion battery positive electrode.
[0195] The button sodium ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the sodium ion battery mentioned above, the negative electrode was a metallic sodium sheet, the separator was glass fiber, and the electrolyte was 1 mol / L NaClO4 dissolved in a solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1.
[0196] Experimental Example 1 Material composition and microstructure characterization
[0197] (1) SEM measurement
[0198] The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor prepared in Example 1 was characterized by emission scanning electron microscopy. Figure 1 As shown, the precursor prepared in Example 1 has a lamellar structure after flash evaporation. The morphology of this lamellar structure is larger than the specific surface area of the stacked structure, which is more conducive to subsequent grinding and refining, and can reach the target particle size faster, thereby improving the synthesis efficiency of the material.
[0199] (2) Detection of sulfur content and doping cation content
[0200] Take appropriate amounts of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor obtained in Examples 1 to 4 and Comparative Examples 1 to 4 and the carbon-coated modified sodium manganese iron phosphate pyrophosphate in a centrifuge tube, add appropriate amounts of hydrochloric acid, heat and digest for 2 hours, then cool and dilute, and measure using an inductively coupled plasma emission spectrometer.
[0201] (3) Determination of iron and phosphorus content
[0202] The iron content was determined by potassium dichromate titration. The metal cation-doped ammonium manganese iron phosphate precursor / lithium manganese iron phosphate obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was decomposed using perchloric acid, and the carbon in the sample was removed at the same time. In an acidic medium, orthophosphate reacted with quinomolybdic acid precipitant to generate a yellow quinoline phosphomolybdic acid precipitate. After filtering, washing, drying and weighing, the weight of the quinoline phosphomolybdic acid precipitate was obtained, thereby converting the phosphorus content in the sample.
[0203] (4) Tap density
[0204] The weighed metal cation-doped ammonium manganese iron phosphate precursor samples of Examples 1 to 4 and Comparative Examples 1 to 4 were placed in a three-sided graduated cylinder and placed in a tap density tester. The test time of the density meter was adjusted. After the tap density tester stopped vibrating, the cylinder was taken out and the readings were read to calculate the tap density of the powder.
[0205] Test data such as Figure 1 And as shown in Table 1.
[0206] Table 1 Tap density, sulfur content, main doping element content ratio and doping element content in the precursor
[0207]
[0208]
[0209] Note: 1438 / Mg means the content of metallic Mg in the precursor is 1438ppm, and the same applies to the others.
[0210] From the data in Table 1, it can be seen that in Examples 1 to 4, the synthesized metal cation-doped ammonium manganese iron phosphate precursor is treated with a phosphate source to prepare a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, and its sulfur content is much lower than that of the metal cation-doped ammonium manganese iron phosphate precursor not treated with a phosphate source in Comparative Examples 1 to 3. This can be attributed to the addition of an appropriate amount of phosphate source to the synthesized metal cation-doped ammonium manganese iron phosphate precursor in Examples 1 to 4, which can induce recrystallization to expose sulfur impurities and detach from the precursor particles, and then through subsequent filtering and washing post-treatment, the transfer of sulfur impurities is achieved, thereby achieving the purpose of removing sulfur impurities, and improving the crystallinity of the precursor, which is beneficial to avoid the introduction of sulfur impurities during the subsequent preparation of carbon-coated modified sodium manganese iron phosphate pyrophosphate. In Comparative Example 4, excessive metal doping affects the electrochemical properties of the positive electrode material. In addition, the addition of a phosphate source can also regulate the content of Mn, Fe, doped metal elements and P elements in the precursor, so that the actual n(Mn+Fe+M): n(P) is slightly less than 1. This regulation optimizes the manganese-iron defects in the lattice of sodium manganese iron pyrophosphate at the molecular level, providing an effective channel for the embedding and extraction of sodium ions; at the same time, the channel is appropriately expanded, the volume change or structural collapse during the sodium storage process is alleviated, and the cycle stability of the material is significantly improved. The ICP test results show that the actual content of the main elements of the precursors synthesized in Examples 1 to 4 and Comparative Examples 1 to 4 is highly consistent with the target doping molar ratio, and the deviation is within a reasonable range. This confirms the accuracy of the ratio of each element in the precursor chemical formula, and proves that the metal cation-doped ammonium manganese iron phosphate precursor was successfully synthesized according to the preset molar ratio of the doped metal element. At the same time, the ICP test also confirmed the uniform distribution of the doping elements in the precursor, laying a solid foundation for the subsequent preparation of positive electrode materials with excellent performance.
[0211] Experimental Example 2 Physical properties of carbon-coated sodium manganese iron phosphate pyrophosphate positive electrode material and physical and chemical properties test of sodium ion battery constructed based on this material
[0212] (1) Electrochemical test
[0213] The carbon-coated modified sodium manganese iron phosphate pyrophosphate material obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was used as the positive electrode active material, and was weighed and dispersed in N-methylpyrrolidone dispersant according to the mass ratio of active material: conductive agent carbon black: binder polyvinylidene fluoride = 90:5:5 to form a uniformly dispersed positive electrode slurry, which was then coated on aluminum foil, vacuum dried at 120°C for 12 hours, and then punched and weighed to obtain a circular pole piece. A metal sodium sheet was used as the negative electrode, the obtained pole piece was used as the positive electrode, glass fiber was used as the diaphragm, and 1 mol / L NaClO4 was dissolved in a volume ratio of 1:1 dimethyl carbonate (DMC) and ethylene carbonate (EC) solution as the electrolyte. A 2032-type sodium ion button cell was assembled in a mikaelona glove box (O2≤0.01ppm, H2O≤0.01ppm), and the electrochemical performance test was performed at room temperature after standing for 12 hours. The test voltage range is set to 1.7~4.3V, and the charge and discharge test is performed at a current rate of 0.2C / 1C. The calculation formula involved is as follows:
[0214] First cycle discharge efficiency = first cycle discharge specific capacity / first cycle charge specific capacity × 100%;
[0215] Capacity retention rate = 100th cycle specific capacity / first cycle discharge specific capacity × 100%.
[0216] (2) Negative electrode manganese content test
[0217] The inductively coupled plasma test method was used to detect the amount of Mn dissolved in the electrolyte of the battery assembled with the carbon-coated modified sodium manganese iron phosphate pyrophosphate positive electrode material obtained in Examples 1 to 4 and Comparative Examples 1 to 4 after cycling 100 times at a current density of 1C.
[0218] (3) Powder compaction density test method
[0219] The carbon-coated modified lithium manganese iron phosphate positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were used as test samples. A powder compaction density meter was used to apply a pressure of 5 T to the powder samples, and the volume and mass thereof were measured to obtain compaction density data.
[0220] The above measurement results are shown in Table 2.
[0221] Table 2 Physical properties of carbon-coated sodium manganese iron phosphate pyrophosphate positive electrode material and physical and chemical performance tests of sodium ion batteries constructed based on this material
[0222]
[0223]
[0224] From the data in Table 2, it can be seen that in terms of compaction density, since comparative examples 1 to 3 did not use a phosphate source to treat the metal cation-doped ammonium manganese iron phosphate precursor, its actual n(Mn+Fe+M):n(P) is slightly greater than 1, and the tap density is <1, which greatly affects the subsequent processing material performance and thus affects the compaction density of the positive electrode material; comparative example 4 is due to the excessive doping of metal cations in the metal cation-doped ammonium manganese iron phosphate precursor. Excessive ion doping causes the particles to grow excessively to form large-sized micron particles, which makes the compaction density of the positive electrode material after crushing smaller.
[0225] The electrochemical performance test further shows that since the metal cation-doped ammonium manganese iron phosphate precursor was not treated with a phosphate source in Comparative Examples 1 to 3, its sulfur impurity content far exceeds the battery-grade standard, and the actual n(Mn+Fe+M):n(P) in the precursor is slightly greater than 1, resulting in a 0.2C capacity lower than that of the corresponding Examples 1 to 3, and the capacity decay is aggravated during the high current 1C and 100 cycles, and the manganese dissolution is aggravated. On the one hand, this is attributed to the fact that the excessively high ratio of manganese, iron and doped metal elements to phosphorus is not conducive to the molecular construction of manganese iron site defects within the lattice of sodium manganese iron phosphate pyrophosphate, and cannot provide a favorable channel for sodium ion migration. On the other hand, due to the large radius of sodium ions, the smaller sodium ion channels cannot well alleviate the stress changes caused by their embedding and extraction processes, and thus the rate performance and cycle stability are poor, and the capacity decay is aggravated. Excessive metal cation doping in Comparative Example 4 greatly reduces the content of active metal sites in the material, thereby reducing the sodium storage capacity of the material; at the same time, the stress changes caused by the embedding and extraction of sodium ions cause the material rate performance and cycle life performance to deteriorate. In contrast, the appropriate amount of metal cation doping in Examples 1 to 4 can effectively exert the synergistic effect between the elements to increase the compaction density of the material (>2.4 g / cm 3 ), first charge specific capacity (>113mAh / g), first coulombic efficiency (>94%) and cycle performance (>96%), while effectively alleviating the manganese dissolution problem (<170ppm) caused by the Jahn-Teller effect.
[0226] In summary, this application successfully prepared a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor. By adding an appropriate amount of phosphoric acid source to the prepared metal cation-doped ammonium manganese iron phosphate precursor, not only the sulfur content of the precursor is significantly reduced, but also the molar ratio of manganese, iron, doping elements and phosphorus elements is regulated to be slightly less than 1, which not only realizes the atomic-level distribution of elements in the precursor, but also improves the tap density, which is conducive to the subsequent preparation of high-performance carbon-coated modified sodium manganese iron phosphate pyrophosphate materials. The sodium ion battery constructed based on this material has excellent charge and discharge capacity, cycle stability and rate performance.
[0227] The preferred implementation manner of the present invention is not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor, characterized in that: The following steps are involved: S1. Using manganese sulfate to provide manganese element to prepare a metal cation-doped ammonium manganese iron phosphate precursor; S2. The metal cation-doped ammonium manganese iron phosphate precursor obtained in step S1 is mixed with the phosphoric acid source solution, the pH of the solution is maintained at 7 to 8, the mixture is fully reacted at 30 to 80° C., filtered, the precipitate is washed, and dried to obtain a low-sulfur metal cation-doped ammonium manganese iron phosphate precursor; Wherein, the metal cation is selected from at least one non-repeating member of Ca, Mg, Al, Ti, Ni, Cr, Zn, Mo, Cu, Zr, Nb, Y, Sn, Co, Ce, V, and W; The low-sulfur metal cation doped ammonium manganese iron phosphate precursor is expressed as NH4Mn x Fe 1-x-y M y PO4, 0<x<0.9, 0<y<0.1; said M represents one or more metal cation doping; The amount of the phosphoric acid source added is at least 0.1 times the amount of the metal cation-doped ammonium manganese iron phosphate precursor; The steps S1 to S2 are all performed under a protective gas atmosphere.
2. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing the metal cation-doped ammonium manganese iron phosphate precursor specifically comprises the following steps: SI. The manganese sulfate, doped metal cation salt solution M is prepared under a protective gas atmosphere to form a mixed solution I; SII. The iron element and the phosphoric acid source solution are fully reacted under a protective gas atmosphere to obtain a ferrous dihydrogen phosphate solution system II; SIII. Under a protective gas atmosphere, the mixed solution I obtained in step SI and the oxidant are added to the dihydrogen phosphate solution system II obtained in step SII, mixed, and fully reacted at 50-80° C. to oxidize the divalent manganese ions and the divalent iron ions to trivalent manganese ions and trivalent iron ions, respectively, to obtain an intermediate system III. After adjusting the pH of the intermediate system III to 7-8, react at 50-80° C., and post-treat to obtain a metal cation-doped ammonium manganese iron phosphate precursor.
3. The low-sulfur metal cation-doped ammonium manganese iron phosphate precursor prepared by the preparation method according to claim 1 or 2.
4. A method for preparing carbon-coated modified sodium manganese iron pyrophosphate, characterized in that: The following steps are involved: Si. The sodium salt, the phosphate source, the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor according to claim 3, the carbon source and the alcohol solution are fully mixed to obtain a slurry, and the obtained slurry is ground and dried to obtain a powder; Sii. Under a protective gas atmosphere, the powder obtained in step Si is pre-calcined at 300-400° C. for 0.5-8 h, then heated to 450-750° C. for full calcination, and post-treated to obtain carbon-coated modified sodium manganese iron phosphate pyrophosphate.
5. The preparation method according to claim 4, characterized in that: In step Si, the molar ratio of the phosphate source, the sodium phosphate salt, and the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor according to claim 3 is 1: (1.3-1.4): (1.3-1.4).
6. The preparation method according to claim 4, characterized in that: In step Si, the carbon source includes one or more of polyethylene glycol, glucose, fructose, sucrose, starch, cyclodextrin, citric acid, tartaric acid, ascorbic acid, malic acid, lactic acid, polyvinyl pyrrolidone, polyvinylidene fluoride, epoxy resin, and phenolic resin.
7. The preparation method according to claim 4, characterized in that: In step Si, the mass ratio of the low-sulfur metal cation-doped ammonium manganese iron phosphate precursor to the carbon source is 1: (0.01-1).
8. Carbon-coated modified sodium manganese iron pyrophosphate prepared by the preparation method according to any one of claims 4 to 7.
9. A sodium ion battery positive electrode, characterized in that: It comprises a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material comprises the carbon-coated modified sodium manganese iron pyrophosphate as claimed in claim 8.
10. A sodium ion battery, characterized in that: It comprises an electrolyte, a separator, a positive electrode and a negative electrode, wherein the positive electrode comprises the positive electrode of the sodium ion battery according to claim 9.
Citation Information
Patent Citations
High-entropy ferric sodium pyrophosphate sodium ion battery positive electrode material and preparation method thereof
CN116404154A
Input device
CN118295543A
Lithium ferric manganese phosphate-carbon composite material as well as preparation method and application thereof
CN116825945A
Ferromanganese phosphate as well as preparation method and application thereof
CN117263158A
Preparation process of battery-grade ammonium ferromanganese phosphate
CN117800306A
Cited By
Lithium manganese iron phosphate precursor and preparation method thereof, lithium manganese iron phosphate, lithium ion battery and electric equipment
CN120440860A
Positive electrode active material and preparation method thereof, positive electrode plate, sodium battery and energy storage device
CN120511285A
Positive pole piece, sodium battery and energy storage device
CN120565587A
Three-dimensional porous carbon coated sodium ferric sulfate positive electrode material, sodium ion battery and preparation method
CN121583895A